A FIB-STEM Study of La0.8Sr0.2MnO3 Cathode and Y2O3-ZrO2/Gd2O3-CeO2 Electrolyte Interfaces of Solid Oxide Fuel Cells. Issue 13 (1st January 2017) - He, Shuai; Chen, Kongfa; Saunders, Martin; Li, Jian; Cui, C. Q.; Jiang, San Ping
Abstract : The interfaces between cathode and electrolyte in solid oxide fuel cells (SOFCs) play a critical role in the overall performance and durability, and are generally formed by pre-sintering at high temperatures, e.g., ∼1150°C in the case of La0.8 Sr0.2 MnO3 (LSM) cathodes. Here the interface between LSM and yttria-stabilized zirconia (YSZ) or Gd-doped ceria (GDC) electrolytes formed under high temperature sintering is studied using Focused Ion Beam and Scanning Transmission Electron Microscope (FIB-STEM) techniques. In the case of LSM/YSZ interface, there is a significant cation interdiffusion, particularly Mn 2+ into YSZ electrolyte in the convex contact ring region and Mn, La and Y cation diffusion along the grain boundary of YSZ electrolyte also occurs. For LSM/GDC interface, no cation interdiffusion was observed. The results indicate the formation of semi-coherent interface, i.e., an atom-by-atom matching only exists locally in regions along the interface, but orientation relationship and lattice mismatch factor between electrode and electrolyte crystallographic planes at the LSM/YSZ and LSM/GDC interfaces vary significantly. Lattice disorientation and misfit of the crystallographic planes occur within a narrow region of 0.10–0.5 nm wide with no amorphous or solid solution formation. The results demonstrate that cation interdiffusion is not an essential requirement for the formation of heterointerfaces for LSM electrode, and disorientation and dislocation of the crystallographic planes at the interface does not impede the oxygen diffusion and incorporation process for the O2 reduction reaction.